Peningkatan Employee Performance Berbasis Employee Engagement pada Karyawan Generasi Z di Semarang - Marlina Manasikana; Mutamimah Mutamimah (Lembaga Yasin AlSys, 2026)
Low levels of employee engagement have impeded the optimal realization of employee performance, particularly among Generation Z employees who are beginning to dominate the workforce in Semarang City and are characterized by a need for a supportive and flexible work environment, as well as attention to employee well-being. This study aims to analyze the effects of work environment and employee well-being on employee engagement and their implications for employee performance among Generation Z employees in Semarang. A quantitative method with an explanatory approach was employed, with data obtained through questionnaires administered to 100 Generation Z employees working in various companies in Semarang, selected using purposive sampling. Data were analyzed using multiple linear regression and mediation testing with the aid of SPSS. The results show that work environment and employee well-being have a positive and significant effect on employee engagement. In addition, work environment, employee well-being, and employee engagement also have a positive and significant effect on employee performance, and employee engagement is proven to mediate the effects of work environment and employee well-being on employee performance. These findings indicate that improving the performance of Generation Z employees can be achieved by creating a conducive work environment and enhancing employee well-being through the strengthening of employee engagement. The implications of this study offer strategic recommendations for companies in managing Generation Z human resources more effectively and sustainably.